SLEEP DISORDERS IN NEUROLOGICAL PRACTICE: A ROLE OF MELATONIN IN THERAPY FOR PRIMARY SLEEP AND AWAKENING DISORDERS IN PATIENTS WITH PARKINSON’S DISEASE - N. V. Fedorova; A. V. Nikitina; Ye. N. Gubanova (Klinicist, 2014)
Sleep and awakening disorders are almost obligate manifestations of Parkinson’s disease. Primary sleep and awakening disorders in Parkinson’sdisease are associated with the degeneration of serotoninergic neurons in the dorsal raphe nucleus and cholinergic neurons in the pedunculopontine nucleus. Impaired awakening maintenance with the development of hypersomnia may result from neuron degeneration in the locus coeruleus or pedunculopontine nucleus. A certain role may be played by the pathological basal ganglionic pulsation caused by striatal dopamine deficiency, which goes to both the thalamic reticular nucleus and pedunculopontine nucleus, as well as by dysfunction of the mesocortical dopaminergic pathways involved in sleep-wake cycle regulation. Synthetic melatonin (Melaxen) is one of the effective medications for the treatment of sleep disorders in Parkinson’s disease. The drug normalizes circadian rhythms and has a hypnotic effect although it is in the usual sense not a soporific agent. Melaxen has a minimum of side effects and is well tolerated by patients from different age groups.